2011
DOI: 10.1002/fld.2586
|View full text |Cite
|
Sign up to set email alerts
|

A consistent and fast weakly compressible smoothed particle hydrodynamics with a new wall boundary condition

Abstract: SUMMARYA modified weakly compressible smoothed particle hydrodynamics (WCSPH) is presented, which utilizes consistent discretization schemes for spatial derivatives in the flow equations. Here, each SPH particle is considered as a computational point that represents a specific part of the fluid. To overcome non-physical oscillations that usually arise in standard WCSPH, we modified the mass conservation equation by using a numerical filter. This modification is based on the difference between two discretizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…The reason for using the ALE technique is to maintain a regular particle distribution as well as a high accuracy. This technique has been proved to be successful in a lot of previous works …”
Section: Ale Particle Methodsmentioning
confidence: 96%
“…The reason for using the ALE technique is to maintain a regular particle distribution as well as a high accuracy. This technique has been proved to be successful in a lot of previous works …”
Section: Ale Particle Methodsmentioning
confidence: 96%
“…Although new semi-analytical approaches to wall boundary conditions are available (Monaco et al, 2011;Fatehi and Manzari, 2011b), the dummy particles theory of Lee et al (2008) has been found to be more compatible for the simulations presented herein. Two layers of dummy particles are arranged close to each wall boundary similar to those particles defined by Lee et al (2008).…”
Section: Boundary Conditionmentioning
confidence: 98%
“…The approximated function f and the kernel W are expressed as (4) and (5) to simplify the notation. In the present work, the quintic Wendland kernel (6) used by Fatehi and Manzari [10] …”
Section: Governing Equationmentioning
confidence: 99%
“…The damping of the spurious oscillation in the pressure field proposed by Fatehi and Manzari [10] is applied to (17). The terms (19) and (20) represent two different formulations for the approximation of the Laplacian of the pressure.…”
Section: ! ð9þmentioning
confidence: 99%
See 1 more Smart Citation